2018
DOI: 10.1080/20008198.2018.1457393
|View full text |Cite
|
Sign up to set email alerts
|

Testing competing factor models of the latent structure of post-traumatic stress disorder and complex post-traumatic stress disorder according to ICD-11

Abstract: With the publication of the International Statistical Classification of Diseases and Related Health Problems, 11th edition (ICD-11) due for release in 2018, a number of studies have assessed the factorial validity of the proposed post-traumatic stress disorder (PTSD) and complex (CPTSD) diagnostic criteria and whether the disorders are correlated but distinct constructs. As the specific nature of CPTSD symptoms has yet to be firmly established, this study aimed to examine the dimension of affect dysregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
2
8
0
1
Order By: Relevance
“…Cloitre, Garvert, Brewin, Bryant, & Maercker, 2013) and symptom structure (e.g. Murphy et al, 2018) of the two ICD disorders has been reported across several different countries and cultures (Karatzias et al, 2018) and is expected to support the clinical utility of the diagnoses at a local and global level. Development of reliable and brief self-report measures for ICD-11 PTSD and CPTSD (Cloitre et al, 2018) have been developed using item response theory and other-related methods (Shevlin et al, 2018).…”
Section: Diagnosis Of Ptsd and Complex Ptsdmentioning
confidence: 83%
See 1 more Smart Citation
“…Cloitre, Garvert, Brewin, Bryant, & Maercker, 2013) and symptom structure (e.g. Murphy et al, 2018) of the two ICD disorders has been reported across several different countries and cultures (Karatzias et al, 2018) and is expected to support the clinical utility of the diagnoses at a local and global level. Development of reliable and brief self-report measures for ICD-11 PTSD and CPTSD (Cloitre et al, 2018) have been developed using item response theory and other-related methods (Shevlin et al, 2018).…”
Section: Diagnosis Of Ptsd and Complex Ptsdmentioning
confidence: 83%
“…What we do not know is how the neurobiological (Lanius & Olff, 2017), psychological (Baekkelund, Frewen, Lanius, Ottesen Berg, & Arnevik, 2018;Schafer, Becker, King, Horsch, & Michael, 2019), affective (Strøm, Aakvaag, Birkeland, Felix, & Thoresen, 2018), and relational (Heeke, Kampisiou, Niemeyer, & Knaevelsrud, 2019;van Dijke, Hopman, & Ford, 2018) alterations associated with different forms, durations, and structures (Armour, Fried, & Olff, 2017;Murphy, Elklit, Dokkedahl, & Shevlin, 2018) of psychotrauma exposure (and reexposure) emerge and take different courses or trajectories across the lifespanand across generations (Burnette & Cannon, 2014;Crombach & Bambonye, 2015;Schick, Morina, Klaghofer, Schnyder, & Muller, 2013). Biopsychosocial mechanisms and processes involved in the long-term adverse impact of childhood trauma over decades into mid-life and old age (Glück, Knefel, Tran, & Lueger-Schuster, 2016) and across generations (Kuffer, Thoma, & Maercker, 2016) have been preliminarily conceptualized but remain understudied.…”
Section: Trauma Exposure and Impact Across The Lifespanmentioning
confidence: 99%
“…Up to now, the studies about CPTSD have been carried out with adult clinical samples (Cloitre et al, 2018 ; Hyland et al, 2017 ; Karatzias et al, 2016 ; Kazlauskas, Gegieckaite, Hyland, Zelviene, & Cloitre, 2018 ; Simon, Roberts, Lewis, van Gelderen, & Bisson, 2019 ; Stadtmann, Maercker, Binder, & Schnepp, 2018 ; van Dijke, Hopman, & Ford, 2018 ), non-clinical community-based samples (Karatzias, Hyland, Ben-Ezra, & Shevlin, 2018a ; Murphy, Elklit, Dokkedahl, & Shevlin, 2018 ), child and adolescent victims of maltreatment (Bertó et al, 2017 ), trafficked children (Ottisova, Smith, & Oram, 2018 ), former child soldiers (Murphy et al, 2018 ), women’s clinical samples (Cloitre, Garvert, Weiss, Carlson, & Bryant, 2014 ; Hyland, Shevlin, Fyvie, & Karatzias, 2018 ), male perpetrators of IPV (Gilbar, Hyland, Cloitre, & Dekel, 2018 ), refugees (Vallières et al, 2018 ) and war prisoners (Zerach, Shevlin, Cloitre, & Solomon, 2019 ). In addition, some of these studies compared PTSD and CPTSD prevalences in the same populations (Cloitre et al, 2014 , 2018 ; Gilbar et al, 2018 ; Hyland et al, 2017 ; 2018 ; Karatzias et al, 2016 ; Murphy et al, 2018 ; Simon et al, 2019 ; Vallières et al, 2018 ; Zerach et al, 2019 ). Despite the fact that IPV is a type of interpersonal violence that is difficult to escape for its particular bond between the survivors and perpetrators, and despite its possible consequences, such as low self-esteem and deconstruction of identity (Hyland et al, 2018 ; Matheson et al, 2015 ; Pill, Day, & Mildred, 2017 ), research on CPTSD in women survivors of IPV is scarce.…”
Section: Ipv Definition and Prevalencementioning
confidence: 99%
“…However, most of this research has been restricted to high-income countries (HICs), whereas significantly fewer studies have analysed samples from low- and middle-income countries (LMICs); e.g. Uganda (Dokkedahl, Ovuga, & Elklit, 2015 ; Murphy, Elklit, Dokkedahl, & Shevlin, 2016 , 2018 ); Angola (Rocha et al, 2019 ); Ghana, Kenya, and Nigeria (Ben-Ezra et al, 2020 ; Owczarek et al, 2020 ); Ukraine (McElroy et al, 2019 ; Shevlin et al, 2018 ); and Lebanon (Hyland et al, 2018 ; Vallières et al, 2018 ). Further research in LMICs is therefore necessary to determine whether ICD-11 criteria for PTSD and CPTSD are internationally relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with aetiological factors associated with CPTSD, trauma experience in these settings is therefore likely to be protracted and impact both adults and children. For example, approximately 40% of adult participants in samples from northern Uganda were abducted in the 1980s as child soldiers, and civil conflict is ongoing in the region (Dokkedahl et al, 2015 ; Murphy et al, 2016 , 2018 ). In the case of South Africa, many people live in communities that are hubs of ongoing trauma, where violence is persistent and pervasive (Kaminer, Eagle, & Crawford-Browne, 2018 ), and many trauma survivors are children (Artz et al, 2016 ; Hsiao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%